Restorative strategies for weakened roots: Systematic review and Meta-analysis of in vitro studies - Corrêa, Gislene; Pradebon Brondani, Lucas; Sarkis-Onofre, Rafael; Dalmolin Bergoli, César (Brazilian Dental Science, 2019)
Objective: This study evaluated fracture resistance values and failure mode of weakened roots restored with cast post and core, fiber post and anatomical posts. Materials and methods: In vitrostudies, published in English, Portuguese and Spanish, that evaluated weakened roots restored with at least two of mentioned strategies were searched for in three databases MEDLINE, PubMed and Scopus until June 2017; there was no restriction regarding the publication year. Fracture resistance values were obtained, and the following comparisons: cast post and core vs. fiber post and vs. anatomical post and fiber post vs. anatomical post were performed. Meta-analyses were conducted using the random effects model to calculate the combined effect of the difference between the averages. Six articles were included in the study. Results: There was no significant difference between the fracture resistance values, but more catastrophic failures were observed on cast post and core, and the included studies presented a low risk of bias for the most domains. Conclusion: It was concluded that weakened roots restored with the searched strategies seem to have similar fracture strength, but fiber and anatomic post decreases the possibility of catastrophic failure. Keywords Review; Root; Dental restoration.